Relationship between insertions of the tibialis anterior and peroneus longus and first tarsometatarsal joint degeneration - Kodai Sakamoto; Mutsuaki Edama; Tomoki Hirai; Hirotake Yokota; Ryo Hirabayashi; Chie Sekine; Tomonobu Ishigaki; Makoto Komiya; Taku Toriumi; Ikuo Kageyama (BMC Musculoskeletal Disorders)
Abstract Background The purpose of this study was to clarify the relationships of the tibialis anterior tendon (TAT) and peroneus longus tendon (PLT) with articular cartilage degeneration on the medial cuneiform and first metatarsal. Methods We examined 100 feet from 50 Japanese cadavers. The TAT was classified into 4 types based on attachment site area and number of fiber bundles: Type I, two fiber bundles with equal (within 20%) attachment site areas on the first metatarsal and medial cuneiform; Type II, with two fiber bundles and a larger (>20%) attachment site area on the medial cuneiform than on the first metatarsal; Type III, with two fiber bundles and a larger (>20%) attachment site area on the first metatarsal than on the medial cuneiform; and Type IV, with three fiber bundles. The PLT was classified into 2 types, following previous studies: Type I, insertion only to the base of the first metatarsal; Type II, insertion to the medial cuneiform and first metatarsal. The severity of articular cartilage degeneration was assessed in five stages using the International Cartilage Repair Society scale. Results No significant difference in severity of articular cartilage degeneration was evident among types of TAT and PLT. Conclusion Our results suggested that anatomical variations in the TAT and PLT might not affect joint stability, indicating that strengthening of these muscles could potentially enhance stability regardless of morphological variations in the insertions.